USED TIRE AS BASE ISOLATOR TIRE FOR EARTHQUAKE RESISTANT HOUSES - Inggemar Särfors (Jurnal Rekayasa Sipil (JRS-Unand), 2011)
The investigation of foundation on tires for absorbing the earthquake energy on houses structure is described here. The foundations are cut cone in shape. There are two tests have been conducted to investigate the shaking energy absorption. First, the foundation is placed on the sand filled tire. The second one, the double tires support round foundation. For comparison purpose, the foundation on sand test without tire is also conducted. The laboratory tests are performed using double hydraulic jack to generate the applied loads. The first jack is used to give the vertical load on the top of foundation to simulate the house load. The other jack is used to produce the load in the horizontal direction to replicate the earthquake load. The results of the tests are plotted in the terms of horizontal load and displacement corves. The double tires foundation shows the higher horizontal displacement-load ratio compared to the others. It indicates that the double tire based foundation absorbing the earthquake energy better than the others. It is concluded that the tired based foundation can be installed to support in the earthquake resistant houses. Keywords: foundation, earthquake resistance, base isolation